Strategi Teknik “Bite & Step” untuk Meningkatkan Keterampilan Sosial Anak Berkebutuhan Khusus di Sekolah - Markus Nanang Irawan (Jurnal Dinamika Sosial Budaya, 2020)
When interacting with others, each person certainly needs a good skill in communication so that the purpose of socializing at school goes smoothly and is achieved. But for student with special needs seems difficult to achieve because they have obstacles or problems in communication. Therefore we need a treatment or assistance called social skills training. The purpose of the study was to determine the effectiveness of the strategy of a game technique called "Bite & Step" to improve social skills in student with special needs so that the effort to interact went smoothly and not be wrong in communicating with friends at school. As participants are groups of student with special needs who have attended elementary school. The research method used is the experimental model in a single case which is the treatment of social skills training using the game technique "Bite & Step" which is then evaluated using graph analysis. The results showed that the technical strategy of "Bite Step" has not been effective for helping to improve the social skills of children with special needs so it needs to be reviewed, evaluated, and retested again